(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SUMMARY: 1. Preliminary remark - 2. The Işık v. Turkey case before the European Court of Human Rights and its background - 3. The previous case-law of the ECtHR in connection with the Işık case - 4. A new protagonist on the Strasbourg stage: The Religious Affairs Directorate - 5. Follow-up cases and subsequent developments – 5.1. ECtHR’s case law – 5.2. Domestic law - 6. Instead of a conclusion: trying to analyse an identity crisis.